MAP4 kinase-regulated reduced CLSTN1 expression in medulloblastoma is associated with increased invasiveness - Ece Sönmez; Shen Yan; Meng-Syuan Lin; Martin Baumgartner (Scientific Reports)
Abstract De-regulated protein expression contributes to tumor growth and progression in medulloblastoma (MB), the most common malignant brain tumor in children. MB is associated with impaired differentiation of specific neural progenitors, suggesting that the deregulation of proteins involved in neural physiology could contribute to the transformed phenotype in MB. Calsynthenin 1 (CLSTN1) is a neuronal protein involved in cell-cell interaction, vesicle trafficking, and synaptic signaling. We previously identified CLSTN1 as a putative target of the pro-invasive kinase MAP4K4, which we found to reduce CLSTN1 surface expression. Herein, we explored the expression and functional significance of CLSTN1 in MB. We found that CLSTN1 expression is decreased in primary MB tumors compared to tumor-free cerebellum or brain tissues. CLSTN1 is expressed in laboratory-established MB cell lines, where it localized to the plasma membrane, intracellular vesicular structures, and regions of cell-cell contact. The reduction of CLSTN1 expression significantly increased growth factor-driven invasiveness. Pharmacological inhibition of pro-migratory MAP4 kinases caused increased CLSTN1 expression and CLSTN1 accumulation in cell-cell contacts. Co-culture of tumor cells with astrocytes increased CLSTN1 localization in cell-cell contacts, which was further enhanced by MAP4K inhibition. Our study revealed a repressive function of CLSTN1 in growth-factor-driven invasiveness in MB, identified MAP4 kinases as repressors of CLSTN1 recruitment to cell-cell contacts, and points towards CLSTN1 implication in the kinase-controlled regulation of tumor-microenvironment interaction.